ADVANTAGES AND DISADVANTAGES OF THE DEVELOPMENT OF DISTANCE EDUCATION IN UZBEKISTAN - Jurabekova Khumora Muzaffar qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights the features, models, advantages and disadvantages of distance education. In addition, obstacles in the development of distance education in Uzbekistan and a critical analysis of the literature on these topics are highlighted. Additionally, the time of COVID-19 has led to increased use of distance learning and social media for educational and communication purposes. The article aims to explore the factors affecting communication and collaboration in distance learning environments in the virtual classroom and beyond during the COVID-19 pandemic, and the role of social networks in this process. In this regard, the article summarizes all the information and knowledge-skills we have collected in this field, and our conclusions and suggestions are given.